Transformasi Program Keluarga Harapan untuk Peningkatan Kesejahteraan di Kota Lhokseumawe - Mauliza, Isratul; Amira, Nadilla; Lestari, Putri; Fazia, Siti; Zulkarnain5, Teuku (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
Program Keluarga Harapan (PKH) is one of the Indonesian government's programs aimed at reducing poverty through conditional cash transfers to poor families. This study aims to analyze the effectiveness of PKH management in improving community welfare in Kota Lhokseumawe. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation of program implementers and PKH beneficiaries. The results of the study indicate that the management of PKH in Kota Lhokseumawe is quite effective, although there are still some obstacles in the aspects of data collection, distribution of assistance, and assistance to beneficiary families. The recommendations of this study emphasize the importance of increasing the human resource capacity of PKH managers, optimizing information technology, and strengthening coordination between agencies to achieve sustainable social welfare goals.